Minimally Invasive Management of Bladder Stones in Children - Esposito, Ciro; Autorino, Giuseppe; Masieri, Lorenzo; Castagnetti, Marco; Del Conte, Fulvia; Coppola, Vincenzo; Cerulo, Mariapina; Crocetto, Felice; Escolino, Maria (Frontiers in Pediatrics, 2021)
Background: Bladder stones (BS) are rare in children. Minimally invasive surgery (MIS) seems to be nowadays the procedure of choice to treat pediatric patients with BS. This study aimed to analyze retrospectively our experience with percutaneous cystolithotomy, endourological treatment with Holmium laser and robotic cystolithotomy in children with BS. Methods: We retrospectively analyzed the data of 13 children (8 boys and 5 girls) with BS who were treated at our centers between July 2013 and July 2020. The patients received 3 different MIS procedures for stones removal: 5 underwent robotic cystolithotomy, 5 underwent endourological treatment and 3 received percutaneous cystolithotomy (PCCL). We preferentially adopted endourological approach for stones < 10mm, percutaneous approach between 2014 and 2016 and robotic approach since 2016 for larger stones. Results: Mean patients’ age at the time of diagnosis was 13 years (range 5-18). Ten/13 patients (76.9%) had primary BS and 3/13 patients (23.1%) had secondary BS. Mean stone size was 18.8 mm (range 7-50). In all cases the stones were removed successfully. One Clavien II post-operative complication occurred following PCCL (33.3%). All the procedures were completed without conversions. Operative time ranged between 40 and 90 minutes (mean 66) with no significant difference between the three methods (p=0.8). Indwelling bladder catheter duration was significantly longer after PCCL (mean 72 hours) compared with robotic and endourological approaches (mean 15.6 hours) (p=0.001). Hospitalization was significantly longer after PCCL (mean 7.6 days) compared with the other two approaches (mean 4.7 days) (p=0.001). The endourological approach was the most cost-effective method compared with the other two approaches (p=0.001). Conclusions: Minimally invasive management of bladder stones in children was safe and effective. Endourological management was the most cost-effective method, allowing a shorter hospital stay compared with the other procedures but it was mainly indicated for smaller stones with a diameter < 10mm. Based upon our preliminary results, robotic surgery seemed to be a feasible treatment option for BS larger than 15-20mm. It allowed to remove the big stones without crushing them with a safe and easy closure of the bladder wall thanks to the easy suturing provided by the Robot technology.